Minoritarian liberalism a travesti life in a Brazilian favela - Silva, Moises Lino e (The University of Chicago Press, 2022)
"What is liberalism? Must it be tied to private property, individualism, and state-granted rights? Can it coexist with poverty, in a space that confines its residents? Can it be produced in a way that upends "traditional" interpretations of success? In this rich ethnography of Rocinha, the largest favela in Rio de Janeiro, Brazil, Moisés Lino e Silva explores what happens when liberalism is inflected by "deviant" subjects, those considered to be outside the bounds of normative understandings of liberty. Such marginalized visions of freedom are here known as "minoritarian liberalism," a phrase that stands in for overlapping, alternative modes of freedom-be they queer, favela, or peasant. The book explores a wide swath of favela dwellers, some of whom are considered "queer"-such as Natasha Kellem, the author's friend and a charismatic self-declared travesti (a gender identity that signifies transition from masculine to feminine)-alongside others that are treated as "abnormal" simply because they live in favelas. Through these multiple, interconnected visions of freedom, Lino e Silva builds an understanding of liberalism that pushes at the boundaries of anthropological inquiry"--
2203
Keywords: Transgender people / Brazil / Rio de Janeiro; Rocinha (Rio de Janeiro, Brazil) / Social conditions; Social conditions; Transgender people; Brazil / Rio de Janeiro; Brazil / Rio de Janeiro / Rocinha